Equivalente funcional entre sanções administrativas e penais e a despenalização de condutas sancionadas no âmbito administrativo - Kuhn, Marcelo Schenkman (2023)
This study addresses the master's dissertation entitled "Functional Equivalence between Administrative and Criminal Sanctions and the Decriminalization of Conduct Sanctioned in the Administrative Scope". The main objective of this work is to analyze the issue of functional equivalence between administrative and criminal sanctions when both have the same purpose. The central problem consists of investigating whether the criminal sanction is truly equivalent to the administrative sanction, considering cases in which both are applied. The research aims to answer two subsidiary questions: (a) is there double jeopardy when both sanctions are applied, and (b) if the purpose of the administrative sanction is sufficient to condemn and penalize a conduct that would also be criminal, is it necessary to impose a dual punishment? The adopted methodological approach is deductive, based on a comprehensive literature review of national and foreign authors, collection of jurisprudence from Brazilian courts, analysis of jurisprudential arguments, and doctrinal and jurisprudential study of crimes provided for in the Penal Code and special penal legislation. The results and conclusions of the research emphasize the need to limit the excessive application of Criminal Law by presenting objective criteria that assist legal practitioners in avoiding unjust penalties that exceed preventive and punitive purposes. Additionally, the functional equivalents of criminal punishment are highlighted, such as the administrative sanction that suffices to achieve retributive and preventive objectives, thereby avoiding double punishment